Preliminary Application of Magnetization Transfer Imaging in the Study of Normal Uterus and Uterine Lesions - Bi, Qiu; Li, Qing; Yang, Jing; Yang, Junyu; Du, Ji; Ding, Fan; Wu, Yunzhu; Wang, Shaoyu; Zhao, Ying (Frontiers in Oncology, 2022)
Purpose: To evaluate the utility of magnetization transfer (MT) imaging in the study of normal uterus and common uterine lesions. Methods: This prospective study enrolled 160 consecutive patients with suspected uterine lesions. Magnetization transfer ratio (MTR) map was obtained by pelvic MT imaging on a 3.0T MRI scanner. Patients confirmed by pathology were divided into normal group and lesion group, according to whether the maximum diameter of the lesion was less than 5mm. After evaluating and eliminating patients with poor image quality by a 3-point Likert scale, MTR values of lesions and normal endometrium, myometrium and cervix were independently measured on the MTR map by two radiologists. Inter-reader agreement was evaluated. MTR values were compared among different uterine lesions and normal uterine structures using the Mann-Whitney U test with Bonferroni correction. Receiver operating characteristic curve was performed. Results: A total of 96 patients with 121 uterine lesions in lesion group and 41 patients in normal group were measured. The MTR values among normal endometrium, myometrium and cervix were statistical significant differences (P < 0.05). There were significant differences between endometrial cancer and normal endometrium and between cervical cancer and normal cervix (P ≤ 0.001). Area under the curve (AUC) for diagnosing endometrial and cervical cancer were 0.73 and 0.86. Myometrial lesions had significantly higher MTR values than endometrial lesions and cervical cancer (both P < 0.001), and the AUC for differentiating myometrial lesions from them was 0.89 and 0.94. MTR values of endometrial cancer were significantly higher than those of cervical cancer (P = 0.02). Conclusions: MTR values showed significant differences among normal uterine structures. It was valuable for diagnosing and differentiating uterine cancer. MTR values could differentiate myometrial lesions from endometrial or cervical lesions.